The impact of working unit and being diagnosed with COVID-19 on secondary traumatic stress level in midwives: A cross-sectional and comparative study - Ayşe Nur Yilmaz; Sümeyye Altiparmak; Yeşim Aksoy Derya (National Scientific Medical Center, 2021)
Aim: This research aims to determine the impact of the unit they work at and being diagnosed with Covid-19 on the secondary traumatic stress level in midwives. Method: Sample of the cross-sectional and comparative research consists of 170 midwives working in a province located in the east of Turkey. The data was collected with Personal Information Form and Secondary Traumatic Stress Scale (STSS). Descriptive statistics, t-test in independent groups and One-way Anova Analysis were used for data analysis. Results: It was determined that 27.1% of the midwives work at Covid service, 28.8% work at community health/family health centres and 44.1% work at other services. It was determined that the rate of midwives who were diagnosed with Covid-19 during the pandemic was 69.4%, the rate of midwives whose close colleagues were diagnosed with Covid-19 was 90.0%. It was found that average scores that midwives get from STSS total and all subdimensions varied statistically significantly between the units they work at (p<0.05) and this variance was caused by midwives working at Covid service and other services. It was determined that average score obtained from STSS total, "avoidance" and "stimulation" subdimensions was statistically significantly lower in midwives who were diagnosed with Covid-19 (p<0.05). In addition, it was determined that average score obtained from STSS total, "emotional violation" and "stimulation" subdimensions was statistically significantly higher in midwives whose close colleagues were diagnosed with Covid-19 (p<0.05). Conclusion: It was determined that midwives working at Covid-19 services experience higher secondary traumatic stress than those working at other services. In addition, while secondary traumatic stress level is higher in midwives whose close colleagues were diagnosed with Covid-19, it was determined that secondary traumatic stress level is lower in midwives who are diagnosed with Covid-19 than those who are not diagnosed.